STUDI KONVERSI BATUBARA MENJADI FRAKSI BAHAN BAKAR CAIR MELALUI PIROLISIS DAN HIDRORENGKAH KATALITIK DENGAN CoMo/ZAA SEBAGAI KATALIS - , NURUL HIDAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A study of coal conversion into fuel fraction have been done via pyrolysis and catalytic hydrocracking to determine the optimum temperature of pyrolysis and effect of the CoMo/ZAA catalyst on the liquid product in the hydrocracking reaction. Coal pyrolysis was performed at variation temperature of 400, 600, 800 and 1000 Â°C. Catalyst CoMo/ZAA was prepared by activation on natural zeolite using HCl 6 N resulting ZAA, followed with impregnation of Mo and Co (1:1) using (NH4)6Mo7â¢6H2O and Co(NO3)2â¢6H2O precursor. The mass of impregnated metal is 1 % (w/w) of the weight of the catalyst. Furthermore the catalyst was calcined and reduced resulted CoMo/ZAA. The CoMo/ZAA catalyst was washed with EDTA resulted CoMo/ZAA(EDTA). Characterization of the catalysts have been done using AAS, FTIR, XRD and surface area analyzer. Thermally hydrocracking without catalyst was performed at temperature of 350, 450 and 550 Â°C, in order to determine the optimum temperature to produce liquid product. Then the catalytic hydrocracking reaction using ZAA, CoMo/ZAA and CoMo/ZAA(EDTA) as the catalyst was done at optimum temperature and at the ratio the catalyst and the feed is 1:10 (w/w). Product of catalytic hydrocracking was analyzed using GC. The results showed that the optimum temperature of pyrolysis in producing coal tar is at a temperature of 600 Â°C that produced a maximum conversion is 48.84%. Optimum product of hydrocracking reaction was achieved at the temperature of 450 Â°C. Catalytic hydrocracking reaction with CoMo/ZAA resulted in the total conversion of 47.01% with 44.59% of it is liquid product while using the CoMo/ZAA(EDTA) as the catalyst resulted total conversion of 47,92% which 46,90% of it is liquid product. From the products of hydrocracking reaction is known that the gasoline fraction is more dominant than diesel fractions and heavy oil fractions.